Evaluation of CFD model predictions of local dispersion from an area source on a complex industrial site. (8th February 2011) - Hill, Richard; Arnott, Alistair; Hayden, Paul; Lawton, Tom; Robins, Alan; Parker, Tim
The CFD model Fluidyn-Panache was configured to model atmospheric transport from an area source. Modelled flow and turbulence were evaluated by comparison with on-site meteorological measurements, whilst atmospheric dispersion was compared with wind tunnel measurements. The results showed that higher rates of vertical and lateral dispersion were modelled than were determined in the wind tunnel, though modelled and measured ground-level centreline concentration data were within a factor of two. Uncertainties in wind tunnel and numerical modelling were highest close to the source. Consideration of fine-scale features was only necessary for receptors in the immediate near-field.